2009
DOI: 10.1159/000262412
|View full text |Cite
|
Sign up to set email alerts
|

Darier-Roussy Sarcoidosis Mimicking Metastatic Breast Cancer

Abstract: Subcutaneous sarcoidosis (also known as ‘Darier-Roussy sarcoid’) is a cutaneous condition characterized by numerous deep-seated nodules on the trunk and extremities. Coexistence of sarcoidosis and breast cancer are reported in the literature, but there will always be a chance of misdiagnosis. It is very crucial to obtain a tissue diagnosis of suspicious metastatic lesions. We report a case of breast cancer presenting with a subcutaneous sarcoid lesion masquerading as a metastatic lesion. A 50-year-old female p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Management of co-existing PTC and SA can be challenging because both of diseases can affect the same organs and the incidences are very similar [4] . An interesting finding of our case is that both diseases were not known by the physician until the time of presentation while in other cases patients are known to have at least one of the disease before cosultation [1] , [2] , [5] . and this make more cofusion for diagnostic workup and need special attension.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Management of co-existing PTC and SA can be challenging because both of diseases can affect the same organs and the incidences are very similar [4] . An interesting finding of our case is that both diseases were not known by the physician until the time of presentation while in other cases patients are known to have at least one of the disease before cosultation [1] , [2] , [5] . and this make more cofusion for diagnostic workup and need special attension.…”
Section: Discussionmentioning
confidence: 72%
“…Sarcoidosis (SA) (flesh-like process) is a multisystemic, idiopathic disease which is characterized by non-caseating epithelioid granulomas mainly involving the lungs (90%), lymph nodes, eyes, and skin [1] . It has a highly variable clinical course [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the literature identified 104 patients diagnosed with breast cancer and sarcoidosis (n = 66) or sarcoid-like reaction (n = 38) [1,8,13,14,18,19,20,21,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. …”
Section: Case Description and Methodologymentioning
confidence: 99%
“…[ 6 ] Many authors theorize that patients with sarcoidosis are predisposed to malignancy, although others believe that malignancy may lead to sarcodosis. [ 7 ] In very rare cases such as ours, both pathologies may coexist in the breast.…”
Section: Discussionmentioning
confidence: 91%